The expression you want to simplify is 0-(x-y).
0-(x-y)
=-(x-y)
=-x+y
You just have to treat the negative sign in front of (x-y) as a -1 and distribute it to both x and -y.
Hey there!
Distance formula:
d =
Plug in variables:
d = ![\sqrt{(0-(-6))+(0-(-7))}](https://tex.z-dn.net/?f=%5Csqrt%7B%280-%28-6%29%29%2B%280-%28-7%29%29%7D)
Simplify.
d = ![\sqrt{6+7}](https://tex.z-dn.net/?f=%5Csqrt%7B6%2B7%7D)
d =
The distance between the two points is
units.
Hope this helps!
0.006
That's you're answer
The reason it would in crese is because they combin their money